2005
DOI: 10.5713/ajas.2005.301
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Genetic Variants of Mitochondrial DNA and Growth Traits in Hanwoo Cattle

Abstract: Genetic variants of Hanwoo mtDNA in the region of cytochrome oxidase subunit I, II and III complex were detected using restriction enzymes. PCR primers were designed based on the bovine mtDNA sequence, and 6 primer sets (Mt4, Mt5, Mt6, Mt7, Mt8 and Mt9) were used. A total of 20 restriction enzymes were used, and 6 restriction enzymes, which were Hinf I, Pvu II, Rsa I, Eco RI, Bgl II, and Msp I, showed genetic polymorphisms. Significant associations between genetic variants and weight traits were observed at WT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Mitochondrial DNA (mtDNA) has been extensively used to investigate the origin and diversification of modern domestic donkey, cattle, and goat populations (Ivankovic et al 2002;Jeon et al 2005;Odahara et al 2006;Sasazaki et al 2006;Liu et al 2007;Lei et al 2007). In the current study, sequence analysis of the cytochrome b (Cytb) gene was applied since this gene contains species-specific information.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial DNA (mtDNA) has been extensively used to investigate the origin and diversification of modern domestic donkey, cattle, and goat populations (Ivankovic et al 2002;Jeon et al 2005;Odahara et al 2006;Sasazaki et al 2006;Liu et al 2007;Lei et al 2007). In the current study, sequence analysis of the cytochrome b (Cytb) gene was applied since this gene contains species-specific information.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its monomorphism, the MT-CYB sequence was not associated with the conformation traits in the raccoon dogs in the present study. Jeon et al (2005) showed significant differences between genotypes identified in the MT-CO2 gene and weight in Hanwoo cattle. Similarly, the results of this study indicate an association between haplotypes (MT-CO1, MT-CO2) and mitochondrial haplogroups as well as body weight and body size of the farmed raccoon dogs.…”
Section: Discussionmentioning
confidence: 89%
“…The association between conformation traits and mtDNA haplotypes has been evidenced as well (Jeon et al 2005;Yen et al 2007;Zhang et al 2008;Chen et al 2009). Statistically significant differences between mtDNA haplotypes and piglet body weight (Yen et al 2007) as well as the height and length of the body in Nanyang cattle have been proved (Zhang et al 2008).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They pointed to the statistically significant relationship of the mtDNA gene СOXII haplotypes and haplogroups with the productive traits of raccoon dogs, such as weight, body size and colour type. Jeon et al (2005) showed significant differences between genotypes identified in the mitochondrial gene COXII and weight in Hanwoo cattle. Results from the Ślaska et al (2016) indicate that the COXII mitochondrial gene may be involved in hair development.…”
Section: Discussionmentioning
confidence: 91%